HUBUNGAN KECERDASAN EMOSI DAN PENYESUAIAN DIRI PADA IBU MUDA YANG MENIKAH DINI - Maylia Pradipta; Ellyana Ilsan Eka Putri (INCARE, International Journal of Educational Resources, 2024)
Level of marriage, by forming a family bound by religion and state based on applicable regulations. Regulations can be violated due to mistakes that are common in society, such as getting pregnant out of wedlock and resulting in early or underage marriages. The aim of the research is to determine the relationship between emotional intelligence and adjustment abilities in young mothers who marry early. This research was conducted on 53 respondents who were mothers married under the age of 20 years and with a maximum marriage age of 5 years. The research uses a quantitative approach method with purposive sampling technique. The data analysis technique uses the Pearson product moment correlation test. The research results obtained a correlation coefficient of 0.520 with a significance value of 0.000 (<0.05), which means there is a correlation between emotional intelligence and the ability to adjust to young mothers who marry early. The research results found that there was a relationship between emotional intelligence and self-adjustment with a fairly strong influence on self-adjustment